Three New Species of Velvety Shore Bugs (Hemiptera: Heteroptera: Ochteroidea) From Mid-Cretaceous Kachin Amber Shed Light on the Evolution of Rostrum Length in Ochteroidea - Zhang, Mao; Zhao, Zhipeng; Ren, Dong; Yao, Yunzhi (Frontiers in Ecology and Evolution, 2022)
Two new genera of velvety shore bugs, Arcochterus Zhang, Ren and Yao gen. nov. and Parvochterus Zhang, Ren and Yao gen. nov. are described, with three new species between them—Arcochterus fuscus Zhang, Ren and Yao sp. nov., Parvochterus reticulatus Ren and Yao sp. nov., and P. lanceolarus Zhang, Ren and Yao sp. nov. Based on the combination of fossil and extant taxa, a cladistic analysis is conducted to confirm the phylogenetic position of these species and allows reconstruction of the inter-genus relationships within the superfamily Ochteroidea. Major conclusions of the phylogenetic analysis: (1) these new species and Grimaldinia pronotalis belong to Ochteridae; (2) Ochteroidea is a monophyletic group, Ochteridae and Gelastocoridae are sister group and monophyletic, respectively. (3) The ancestral character state reconstruction (ACSR) shows that the length of the rostrum has occurred in at least three independent transitions during the evolution of the superfamily Ochteroidea.